Blocks - Based Data Hiding Approach for Electronic Cheque Authentication - Zeydan, Hiba Z (Al-Nahrain Journal of Science, 2012)
This research, suggests a combination of digital representation and authentication methods to electronically transfer the typical paper-based bank cheque between banks over open and insecure computer networks like Internet. This proposed combination would be a sender – receiver protocol. At the sender side, a scanned colored image of the bank cheque would be transformed to a binary image, and a sequence of bits would be extracted from it and embedded back into it again as a content-dependent authentication signature (AS) which would be computed by using some image data and a secret key. At the receiver side, the AS would be extracted from the signed binary cheque image (the host image) in order to verify the cheque’s authenticity; and to locate any illegal alterations that may be done in the host image by malicious hackers during the transmission. Both AS extraction and embedding methods are blocks-based methods in order to locate the exact blocks where the undesirable modifications may be done in the host image. Some experimental results and mathematical metrics would be tested to demonstrate the validity of the suggested data hiding approach. The conclusions would show that this suggested approach can be used to electronically sign the binary cheque image without causing noticeable loss of its visual quality; and with much storage and band saving during the electronic transfer between the sender and the receiver.